2017
DOI: 10.1021/acschembio.7b00097
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous Production and Yield Improvement of Epothilones in Burkholderiales Strain DSM 7029

Abstract: The cloning of microbial natural product biosynthetic gene clusters and their heterologous expression in a suitable host have proven to be a feasible approach to improve the yield of valuable natural products and to begin mining cryptic natural products in microorganisms. Myxobacteria are a prolific source of novel bioactive natural products with only limited choices of heterologous hosts that have been exploited. Here, we describe the use of Burkholderiales strain DSM 7029 as a potential heterologous host for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 58 publications
0
51
0
1
Order By: Relevance
“…The epothilones are potent anticancer drugs that bind to tubulin and inhibit the disassembly of microtubules (Bian et al, 2017). The epothilone B derivative ixabepilone has been approved for use in the treatment of breast and ovarian cancer patients, showing remarkable curative effect compared with taxol (Roché et al, 2007;Thomas et al, 2007;Sparano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The epothilones are potent anticancer drugs that bind to tubulin and inhibit the disassembly of microtubules (Bian et al, 2017). The epothilone B derivative ixabepilone has been approved for use in the treatment of breast and ovarian cancer patients, showing remarkable curative effect compared with taxol (Roché et al, 2007;Thomas et al, 2007;Sparano et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, only the essential elements for promoter were found in the P3 promoter, and only the P3 promoter showed strong transcriptional activity. The complete genome of the epothilone-producing strain S. cellulosum So0157-2 was sequenced (Schneiker et al, 2007;Han et al, 2013;Bian et al, 2017), the Fis family regulatory protein was identified (Schneiker et al, 2007;Zhu et al, 2012), and the binding activity of this regulatory protein epothilone biosynthesis promoter was confirmed by EMSA assay in vitro. The binding activity of Etf1 with epothilone biosynthesis promoter was demonstrated by the co-expression of Etf1 and the promoter ligated with reporter gene EGFP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To simultaneously assess large numbers of closely related bacterial strains and their pan-metabolomes, molecular networking should be improved to recognize the MS/MS fragmentation patterns with the availability of biosynthetic gene gene clusters (14,36). The exploitation of secondary metabolic gene clusters requires the continuous development of transgenic cluster techniques among different organisms, including the optimization of super-hosts and the improvement of the methods for constructing/expressing multiple genes in heterologous systems (37,38).…”
Section: Activating Cryptic Gene Clusters Through Genetic Manipulationsmentioning
confidence: 99%
“…epothilone C 34) has been significantly improved using a novel electroporation procedure. 23 30 As iron complexes are generally poor catalysts for C-H amination, it is believed that the enzyme's protein framework provides function that the iron cofactor cannot achieve alone.…”
mentioning
confidence: 99%